ln(x-4)=6

Simple and best practice solution for ln(x-4)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-4)=6 equation:


Simplifying
ln(x + -4) = 6

Reorder the terms:
ln(-4 + x) = 6
(-4 * ln + x * ln) = 6
(-4ln + lnx) = 6

Solving
-4ln + lnx = 6

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-6 + -4ln + lnx = 6 + -6

Combine like terms: 6 + -6 = 0
-6 + -4ln + lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= | | -82=-2(6-5r) | | 18y^2-18x^3+2-18y^4-18x^5= | | 5(3x+7)-11=54 | | (-8)(-2)= | | 5+4p-8p=-19 | | 14y^3-4x^2+2-6y^3-2x^2= | | x^2+10x+-4=0 | | -9x-8=1x+16 | | 2x=(7x-y) | | 1+2n+6n=-7 | | 7x+96=-5x | | 368317*8= | | 20/x=4/9 | | 415441*9= | | -23=6-5n-4 | | 415441*10= |

Equations solver categories